Mycorrhizal Symbiosis for Better Adaptation of Trees to Abiotic Stress Caused by Climate Change in Temperate and Boreal Forests - Usman, Muhammad; Ho-Plágaro, Tania; Frank, Hannah E. R.; Calvo-Polanco, Monica; Gaillard, Isabelle; Garcia, Kevin; Zimmermann, Sabine D. (Frontiers in Forests and Global Change, 2021)
Global climate changes have serious consequences on natural ecosystems and cause diverse environmental abiotic stressors that negatively affect plant growth and development. Trees are dependent on their symbiosis with mycorrhizal fungi, as the hyphal network significantly improves the uptake of water and essential mineral nutrients by colonized roots. A number of recent studies has enhanced our knowledge on the functions of mycorrhizal associations between fungi and plant roots. Moreover, a series of timely studies have investigated the impact and benefit of root symbioses on the adaptation of plants to climate change-associated stressors. Trees in temperate and boreal forests are increasingly exposed to adverse environmental conditions, thus affecting their durable growth. In this mini-review, we focus our attention on the role mycorrhizal symbioses play in attenuating abiotic stressors imposed on trees facing climatic changes, such as high temperatures, drought, salinity, and flooding.